POTENTIAL UTILIZATION OF SOLID LIPID NANOPARTICLES AS A SOLUTION TO OPTIMIZE THE BIOAVAILABILITY OF ANTIDEPRESSANT DRUG SSRI IN IMPROVING THE EFFECTIVENESS OF DEPRESSION TREATMENT: A LITERATURE REVIEW - Dyson, Nathaniel Gilbert (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2024)
Background: Currently, more than 264 million people globally suffer from major depressive disorder. Pharmacological treatments that are the main choice in cases of depression such as antidepressants are still constrained by low bioavailability, especially in the brain. Recent research shows the potential of solid lipid nanoparticles (SLN) as a specific antidepressant drug carrier agent and is able to increase bioavailability in the brain. Methods: This literature review was compiled based on article searches in international databases, such as PubMed, Scopus, and Cochrane for the last 10 years until November 11, 2022. Study inclusion criteria included clinical and in vitro studies that measured differences in bioavailability of antidepressant drugs with and without SLN. Discussion: In the research that has been conducted to date, it is known that SLN can carry duloxetine through the blood brain barrier effectively. This is evidenced by the behavioral despair test and BDNF concentrations that show a significant cure for depression and can match normal or control rats. In addition, in the biosafety test, SLN has also been shown to be safe for use in in vitro and in vivo experiments, namely through dermal administration mainly, and oral and parenteral, although it still requires further study. Conclusion: In conclusion, SLN is a very potential solution to optimize the bioavailability of SSRI antidepressant drugs. Further clinical research is needed to confirm the efficacy and safety of using SLN as a carrier for antidepressant drugs in humans, especially in oral and parenteral administration due to the lack of data to date.